microRNA-144/451 decreases dendritic cell bioactivity via targeting interferon-regulatory factor 5 to limit DSS-induced colitis - Lin, Zhijie; Xie, Xiaoyan; Gu, Min; Chen, Qian; Lu, Guotao; Jia, Xiaoqin; Xiao, Weiming; Zhang, Jun; Yu, Duonan; Gong, Weijuan (Frontiers in Immunology, 2022)
The microRNAs miR-144/451 are highly conserved miRNA that is strongly induced during erythropoiesis. Despite the biological functions of miR-144/451 have been extensively studied in erythropoiesis and tumorigenesis, few studies have been conducted in immune responses. In this study, we showed that miR-144/451-/- DCs exhibit increased activation. Mechanistically, the miR-144 directly targets the 3`-UTR of IRF5 and represses the expression of IRF5 in DCs. Ectopic expression of miR-144/451 by lentiviruses downregulates the levels of IRF5 and suppresses DCs function. In addition, knockdown of IRF5 by shRNA significantly inhibits activities of the miR-144/451-/- DCs. Expression of miR144/451 was decreased in DCs from both patients with IBD and mice with DSS-colitis compared with controls. Human PBMC derived DCs were downregulated expression of miR144/451 after LPS stimulation. In the DSS-induced colitis mice model, we showed that ablation of the miR-144/451 gene causes severe colitis, and their DCs from both periphery and MLN expressed higher co-stimulatory molecules and pro-inflammatory cytokines than wild-type mice. In addition, DCs isolated from miR-144/451-/- mice transfusion exacerbates mice colitis. In the bone marrow transplanted chimeric mice model, we show that miR-144/451-/- bone marrow transplantation deteriorated DSS-induced colitis. At last, we treat the mice with miR-144/451 delivered by chitosan nanoparticles revealing protective effects in DSS-induced colitis mice. Thus, our results reveal a novel miR144/451-IRF5 pathway in DCs that protects experimental colitis. The manipulation of miR-144/451 expression and DCs activation in IBD patients may be a novel therapeutic approach for the treatment of inflammatory diseases.